2014
DOI: 10.3109/01902148.2014.938200
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-based angiotensin-converting enzyme 2 in treatment of acute lung injury rat induced by bleomycin

Abstract: This research provided clues for the development of effective therapeutic methods to ALI using stem cell transplantation and gene therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Lung TNF‐α mRNA level was also decreased by umbilical cord MSCs in the other Moodley et al study [24]. In the Gao et al study, MSC therapy increased TNF‐α protein level when measured 13 days after MSC administration but not at earlier time points [14]. There was no change in TNF‐α protein level in the Min et al study [25].…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Lung TNF‐α mRNA level was also decreased by umbilical cord MSCs in the other Moodley et al study [24]. In the Gao et al study, MSC therapy increased TNF‐α protein level when measured 13 days after MSC administration but not at earlier time points [14]. There was no change in TNF‐α protein level in the Min et al study [25].…”
Section: Resultsmentioning
confidence: 94%
“…Improvement in fibrosis was reported in six studies [11, 12, 18, 20, 22, 23], and a decrease in inflammation was reported in five studies [15, 16, 18, 24]. The Gao et al study reported less improvement with MSCs alone than with MSCs transfected with ACE2 [14]. Thus, substantial improvement was seen in 11 of 12 studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations